New peculiar approach to resource economies in induction motor design - Muravlev (Muravlyov) O. P. Oleg Pavlovich (1999, 1999)
At the design stage of modern induction motors (IM) the potentialities to increase both electrical and magnetic loads on the basis of available materials turned out to be exhausted. Given the available approach to design of electrical machines of different kinds of IM, including all parameters, are considered to be determinate. The investigations carried out in production technology showed that marked spread parameters and quality indices take place that should be taken into consideration in design. Spread parameters in design are taken into account by an indirect route-providing a reserve in quality indices. In turn it causes material capacity increase. The purpose of the paper is development of a peculiar approach to resource economies in IM design on the basis of parameter spread decrease especially when prices change quickly during the transition stage of the economy. An actual decrease of spread parameters is possible when manufacturing batch-produced electrical machines using modern equipment with effective checking system